Cancer of the ampulla of Vater: chromosome 17p allelic loss is associated with poor prognosis. Issue 6 (1st June 2000) - Scarpa, A; Di Pace, C; Talamini, G; Falconi, M; Lemoine, N R; Iacono, C; Achille, A; Baron, A; Zamboni, G
Abstract : BACKGROUND: Cancer of the ampulla of Vater kills 60% of affected patients. Local spread of the tumour (T stage) is the only reliable prognostic factor. Nevertheless, any cancer stage includes long term survivors and patients dying from the disease. The molecular anomalies involved in this process have the potential to serve as additional prognostic markers. AIM: To evaluate if allelic losses (LOH) of chromosomes 17p and 18q may be of prognostic value in multivariate survival analysis. METHODS: We examined 53 ampullary cancers for chromosome 17p and 18q LOH using microsatellite markers and DNA from paraffin embedded tumours. All patients were treated by surgery alone (pancreaticoduodenectomy). Multivariate survival analysis included age, sex, tumour size, macroscopic appearance, grade of differentiation, T stage, lymph node metastasis, and chromosome 17p and 18q status. RESULTS: Chromosome 17p and 18q LOH were detected in 28 (53%) and 18 (34%) cancers, respectively. Multivariate survival analysis indicated chromosome 17p status as an independent prognostic factor together with T stage. The five year survival for chromosome 17p retention and 17p loss was 80% and 7%, respectively. The risk of death from cancer within the five year follow up period for patients with cancers harbouring chromosome 17p LOH was 11 times higher than that of patients with cancers retaining chromosome 17p (p<0.0001), regardless of the tumour stage at diagnosis. CONCLUSIONS: Chromosome 17p status is an independent prognostic factor among ampullary cancers at the same stage. The combined use of T stage and chromosome 17p status may help in deciding whether ampullary cancer patients require additional therapy other than surgery alone.